Ionic Liquids in Refinery Desulfurization: Comparison between Biphasic and Supported Ionic Liquid Phase Suspension Processes - Kuhlmann, Esther; Haumann, Marco; Jess, Andreas; Seeberger, Andreas; Wasserscheid, Peter (Chemsuschem, 2009)
The desulfurization of fuel compounds in the presence of ionic liquids is reported. For this purpose, the desulfurization efficiency of a variety of imidazolium phosphate ionic liquids has been tested. Dibenzothiophene/dodecane and butylmercaptan/decane mixtures were used as model systems. Single-stage extractions reduced the sulfur content from 500ppm to 200ppm. In multistage extractions the sulfur content could be lowered to less than 10ppm within seven stages. Regeneration of the ionic liquid was achieved by distillation or re-extraction procedures. Supported ionic liquid phase (SILP) materials, obtained by dispersing the ionic liquid as a thin film on highly porous silica, exhibited a significantly higher extraction performance owing to their larger surface areas, reducing the sulfur content to less than 100ppm in one stage. Multistage extraction with these SILP materials reduced the sulfur level to 50ppm in the second stage. The SILP technology offers very efficient utilization of ionic liquids and circumvents mass transport limitations because of the small film thickness and large surface area, and allows application of the simple packed-bed column extraction technique.